Ultra-high performance concrete: A review of its material properties and usage in shield tunnel segment - Fangyuan Niu; Yuhang Liu; Fangchen Xue; Hao Sun; Tong Liu; Haijun He; Xuguang Kong; Yunteng Chen; Hongjian Liao (Case Studies in Construction Materials)
Ultra-high performance concrete (UHPC), as a recent advancement in concrete technology, boasts exceptional durability and mechanical properties. Its widespread application in housing, bridges, and tunnels significantly enhances the overall structure and durability of buildings. This paper summarizes the material composition and working performance (Compressive, tensile, impact and durability properties) of ultra-high performance concrete. In view of its important role in underground engineering field, it has excellent effect in shield tunnel segment reinforcement. Therefore, the reinforcement methods of shield tunnel segment and the reinforcement process of Ultra-high performance concrete are discussed, and the failure modes of Ultra-high performance concrete reinforcement are evaluated. The overall structural characteristics, segment joints, positive and negative bending moments of the segment are analyzed respectively. At present, it is concluded that long-term performance and related features need to be further studied. This study will help alleviate the shortcomings of shield segment reinforcement technology and methods, and further encourage the wide application of Ultra-high performance concrete in tunnel engineering.